Pengaruh Audit Tenure dan Financial Distress pada Audit Delay dengan Spesialisasi Auditor Sebagai Variabel Pemoderasi - Sawitri, Ni Made Dwi Candra; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
The purpose of this research is to analyze the auditor specialization to moderate the influence of audit of tenure and financial distress on audit delay at mining company in Indonesia Stock Exchange year 2012-2016. The sample is determined using purposive sampling method. The population of this study amounted to 42 companies. Researched as many as 25 companies from 32 companies included in the sample. This research uses technique of data analysis of Moderating Regression Analysis (MRA) test. The result of this research is that the auditor specialization does not moderate the influence of audit audit on audit delay. Specialization of auditors weakens the influence of financial distress on audit delay. Tenure audit has no effect on audit delay. Financial distress positively affects the audit delay. Keywords : Audit tenure, financial distress, audit delay, auditor specialization